Influences of the human milk bank in the maintenance of human breastfeeding of premature newborns, from a maternal perspective (Research, Society and Development, 2022)
Objectives: to identify the influences of the HMB for the maintenance of human. Methods: this is a descriptive study with a qualitative approach, based on Bardin's content analysis. The research was carried out in a public maternity hospital in a municipality of Pernambuco, accredited as the Baby-Friendly Hospital Initiative (IHAC), breastfeeding of PTNBs, from a maternal perspective, which has its own HMB called BIAMA and is a reference maternity. It had the participation of nine mothers of PTNB hospitalized and who used the services of the HMB, who agreed to sign the TCLE. The research was approved under Opinion n. 033283/2021 and CAAE 45353321.5.0000.5201. Results: when the speeches were categorized, three categories emerged: guidelines on human milk and lactation management; pasteurized milk from donors and social support, which will be detailed throughout the article. Conclusions: Human breastfeeding of PTNBs is a great challenge for lactating women and professionals involved in the care of these patients. The HMB has a very important role in guiding, leading in the handling of massage and breast milking to encourage increased milk production and thus meet the demand of these hospitalized PTNBs, in addition to counting on the donation and processing of donated milk as fundamental aspects. in encouraging and supporting human breastfeeding.